Kontribusi Need to Belong terhadap Self-Persentation Online pada Remaja di Media Sosial - Annafiah, Siti; Mardianto, Mardianto (Lembaga Yasin AlSys, 2025)
This study aims to examine the contribution of the need to belong to self-presentation online among adolescents actively using social media. The need to belong is a psychological need to be accepted and become part of a social group, while self-presentation online refers to individuals’ efforts to construct their self-image on social media. This research employs a quantitative method with a correlational design. The sampling technique used in this study is purposive sampling, and data were collected through an online questionnaire involving 120 respondents aged 15-22 years who actively use social media. The data were collected using a Likert scale model and analyzed using simple linear regression analysis. The results show a significant positive relationship between the need to belong and self-presentation online, with a contribution value of 22.8%. This indicates that the higher an individual’s need to feel accepted, the greater their tendency to shape and adjust their self-image displayed on social media. These findings suggest that self-presentation online is influenced not only by technical or aesthetic factors but also by the psychological need to be accepted by social groups.